The Impact of Working Capital Management on Investment Efficiency: Evidence from Emerging Countries - Ilker YILMAZ (Eurasian Journal of Business and Economics)
This article aims to investigate the impact of the firm’s working capital management policies and practices on the efficiency of their investments. The sample consists of 6016 non-financial firms and the data have been collected for the period from 2009 to 2021. We conducted pooled ordinary least squares (OLS) regression, and panel regression and employed the generalized method of moments to explore the dynamic nature of the relationship. The results revealed that, in static models, pooled OLS regression showed a positive relationship between CCC and investment efficiency, whereas panel regression reported a negative relationship. A similar case is confirmed by the dynamic models. The non-linear models which include the square of CCC confirmed an inverted U-shape relationship, implying an optimal level of CCC. The findings of the study are expected to have implications for corporate managers, the users of financial statements, as well as policymakers and regulatory bodies. To the best of our knowledge, this is the first empirical study investigating the impact of working capital on investment efficiency. It makes an original contribution to the literature by presenting novel empirical evidence on the topic from emerging countries in a multi-country and multi-industry context.